2007
DOI: 10.1007/978-3-540-71035-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Space-Sharing on SDSC’s DataStar System

Abstract: Abstract.Using a large HPC platform, we investigate the effectiveness of "symbiotic space-sharing", a technique that improves system throughput by executing parallel applications in combinations and configurations that alleviate pressure on shared resources. We demonstrate that relevant benchmarks commonly suffer a 10-60% penalty in runtime efficiency due to memory resource bottlenecks and up to several orders of magnitude for I/O. We show that this penalty can be often mitigated, and sometimes virtually elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…We also found that pairing communication-bound applications may yield acceptable slowdown [15] [20]. While our work focused on computation and communication performance, the study in [18] focused on memory and I/O, confirming the benefits from coscheduling. However, there are also cases where an application can exploit the performance potential of all cores per node well and space sharing may perform better.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…We also found that pairing communication-bound applications may yield acceptable slowdown [15] [20]. While our work focused on computation and communication performance, the study in [18] focused on memory and I/O, confirming the benefits from coscheduling. However, there are also cases where an application can exploit the performance potential of all cores per node well and space sharing may perform better.…”
Section: Introductionsupporting
confidence: 62%
“…In earlier work, we have shown that better results may be obtained if rather using the additional cores for other applications with complementary characteristics [14][16] [20], as also found by other researchers [18]. We call such resource allocation semi time sharing since the cores are partitioned among the applications, i.e.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations